The effectiveness of using simulation strategy in developing Arabic calligraphy skills for eighth grade students in the Capital Municipality - Al-Lahabi, Abdulkareem Ali Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the effectiveness of using the simulation strategy in developing Arabic calligraphy skills among the eighth grade students of the basic education stage in Amanat Al-Asimah. The tools were given to specialized arbitrators to judge their validity. The study sample consisted of (100) male eighth-grade students, and they were equally distributed into two groups (experimental and control), chosen randomly from (Zayd bin Haritha) school, and the study was applied in The second semester of the academic year (2021- 2022 AD), The results of the study showed that there was a significant statistical difference at the significance level (0.05) between the mean scores of the experimental group in the pre and post applications to test Arabic calligraphy skills in favor of the post test, due to the effectiveness of the simulation strategy in teaching Arabic calligraphy skills.
Keywords: strategy; simulation; Arabic calligraphy